Effect of rice husk additions on the final composition of fired kaolinite ceramic - Azlin Fazlina, Osman; Syed Nuzul Fadzli, Syed Adam (Universiti Sains Malaysia (USM), 2008)
Organized by School of Materials and Mineral Resources Engineering, University Sains Malaysia (USM), 10th - 11th April 2007 at Penang.